Metrical fairy-tales. Mario Benedetti’s anapests in Vanno via i tuoi occhi (inOpera Esercizi di lettura su testi contemporanei, 2025)
This paper presents a metrical and thematic analysis of Vanno via i tuoi occhi by Mario Benedetti, starting from a single detail: the epigraph from La luna e i falò, «era morta la vecchia del Nido». The first section explores the connection between tragic aspects in Pavese and elegiac elements in Benedetti, focusing on the mythical and fairy-tale features. The aim is to determine whether Pavese’s influence extends to the metrical structure. The second section develops a generative account using Bracketed Grid Theory by Fabb and Halle (2008). The goal is to hypothesize an underlying anapaestic structure and connect it with fairy-tale and elegy elements.
Keywords: Mario Benedetti; Cesare Pavese; Metrics; Anapaest; Elegy; Fairy-tale